ENHANCING VENTILATION IN URBAN STREET CANYON ENVIRONMENTS USING ADJUSTABLE WIND FLOW DEFLECTORS - Vasudevan, Madhavan (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2025)
Near-road buildings in densely built environments experience poor air quality due to traffic emissions and passive mitigation strategies are widely considered to tackle the concern. Despite the dynamic nature of the urban environment, passive interventions have been largely introduced in a static setup in the past; the risk of them offering counter-productive results under conditions they are not designed for and the opportunity to adapt them to the local environment is a research area that deems further exploration. However, developing solutions on a case-to-case basis is a computationally impractical exercise, and the applicability of such solutions in a real-street environment would be far from being straightforward. Therefore, the current study has been conducted to offer a methodology to develop adaptive passive interventions, wind deflectors, from both quantitative and qualitative standpoints; quantitative through evaluation of personal exposure to pollutants and qualitative through assessment of pollution removal mechanisms respectively. The performance analysis of adjustable wind deflectors in this study corroborates their conceptualization, sensitivity to environmental variables and practicality for their deployment in a real-street environment. Wind deflectors in 2D urban and 3D city-type environments maneuvered average street canyon concentrations ( Ccanyon) by regulating the amount of pollution removed from the same through mean (PCHmean) and turbulent fluctuations (PCHfluc) induced fluxes. Results from both 2D and 3D simulations provided sufficient evidence for the hypothesis conceived in the work that if the ambient above-roof winds were deflected optimally into the street canyons to maximize PCHmean, a lower Ccanyon could be achieved by reducing the dependence on turbulence that facilitated relatively localized pollution removal. Apart from analyzing the removal mechanisms through mean and turbulence-induced fluxes, field synergy theory was applied to the performance assessment of wind deflectors for asymmetric city-type environments. A higher field synergy (resulting in a high field synergy number, FSn and Sherwood number, sh) meant enhanced synergy between velocity and concentration fields, and therefore an increased pollution removal by convective fluxes and reduced dependence on the diffusive fluxes for the same. The inverse correlation between Sh and Ccanyon supported the notion that convective fluxes aided in facilitating a global clean-up of the street canyons and that it is beneficial to maximize the same. It also saliently demonstrated that the wind deflectors were effective in regulating pollution removal through convective and diffusive fluxes as they were PCHmean and PCHfluc. As with the conceptualization of the adjustable wind deflectors, their sensitivity was firstly evaluated under 2D settings by evaluating the ventilation performance of the deflectors when placed at different positions at the roof level between the leeward and windward facades. In a specific configuration when the deflector was 2m away from the leeward facade, Ccanyon was reduced by 2.84 folds. Furthermore, in another specific configuration where the deflector was positioned 0.25m from the leeward facade, counterbalancing vortices were generated within the street canyons which facilitated washdown along both the leeward and windward facade resulting in an 86.5 and 8.45% exposure reduction along the same. The performance sensitivity was extended to ideal and asymmetric city-type (step-up, step-down and steep) street canyon environments for differing pollution source configurations, Cross Road Pollution (CRP) and Side Road Pollution (SRP) source models. These models were considered to represent the diurnal changes in traffic flow directions. For an ideal city-type environment, the wind deflectors performed modestly for the CRP source model by reducing 7%, 11% and 13% of CO exposure on the leeward wall, upwind side wall and downwind side wall without affecting the windward wall of the target street canyon. Whereas for the SRP source model, it reduced 91%, 32% and 34% on the same with a 17% reduction on the windward wall of the target street canyon. Furthermore, the concept of an adjustable deflector system was demonstrated to mitigate prolonged high exposure for building occupants exposed to changing traffic emission sources via all the surrounding building facades and at the ground by considering 4 linearly interpolated cases from the CRP and SRP source models including 0, 8, 16 and 24 hours of CRP in day and rest SRP. Mixed results were obtained for asymmetric city-type street canyons. For the step-down canyon, the deflectors promoted pollution reduction in building facades by 73.55% and 34.79% from leeward and windward walls under a Cross Road Pollution (CRP) source. A 16.57% pollution exposure was reduced on side walls under a Side Road Pollution (SRP) source. However, apart from the 13.87% CO reduction across windward walls under the CRP source, the wind deflectors predominantly resulted in detrimental results for step-up canyons. Another layer of complexity was added to the steep street canyons by considering changes in wind direction in tandem with traffic flow changes. To handle the changes in wind direction, the tilted configuration of wind deflectors was tested where they were tilted about their optimal locations to deflect the ambient winds perpendicularly. A combined multi-parameter sensitivity was conducted to evaluate the risk of using no deflectors as opposed to using deflectors that could only be positioned at the optimal location based on the traffic emission source and deflectors that could be both positioned at the optimal location based on the traffic source and be tilted according to the wind direction. These scenarios were evaluated for their impact on the leeward, windward and side facades under 16 linearly interpolated scenarios from 0, 8, 16 and 24 hours of CRP in day and rest SRP and 0, 8, 16 and 24 hours of orthogonal winds and rest obliquely respectively. The results indicated that although the tilted configuration of the deflectors only imparted a modest influence on the windward and the side facades, they reduced exposure across the leeward in the target street canyon by 47.3% and 62.2% under CRP and SRP source models respectively. Finally, considering the dynamism of the street canyon environment, and the challenges associated with implementing a dynamic adjustable wind flow deflector that is sufficiently responsive to the rapidity of changes in the environment, a multidirectional wind deflector design was introduced. They were evaluated for efficacy in diverting ambient winds that are parallel, perpendicular and oblique at 45 to the street canyon under study, with a common multi directional wind deflector design. The design was efficient in enhancing ground level ventilation for parallel ambient winds while under orthogonal and oblique winds, the leeward and windward walls experienced generally positive and negative impacts respectively based on their relative location in the street canyon. Further, based on Weibull distribution for wind flow in Dublin city centre and meteorological wind data recorded for six months at the Dublin Airport, the efficacy of multi-directional wind deflector was evaluated for predominant flow conditions in Pearse Street neighborhood in Dublin, Ireland. The multi directional wind deflectors modestly reduced about 15% CO exposure across the target leeward facades while it developed mixed implications with a modest detriment to improvement between -20% and 16% on various target windward facades. Finally, the major outcomes from the work were utilized to conclude the scope of potential, inherent limitations of the analyses conducted, implications under usage and further opportunities for improved understanding of the functionality of the wind deflectors and deployment of the same in future.
APPROVED
Keywords: Street canyons; Adjustable wind flow deflectors; Computational Fluid Dynamics